2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7318373
|View full text |Cite
|
Sign up to set email alerts
|

Sleep stage classification based on respiratory signal

Abstract: One of the research tasks, which should be solved to develop a sleep monitor, is sleep stages classification. This paper presents an algorithm for wakefulness, rapid eye movement sleep (REM) and non-REM sleep detection based on a set of 33 features, extracted from respiratory inductive plethysmography signal, and bagging classifier. Furthermore, a few heuristics based on knowledge about normal sleep structure are suggested. We used the data from 29 subjects without sleep-related breathing disorders who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Respiration monitoring during sleep is particularly useful. For example, the respiration signal can be used to infer the person's sleep stages (light, deep or REM sleep) [47,21,39] and diagnose sleep disorders [4,12].…”
Section: Introductionmentioning
confidence: 99%
“…Respiration monitoring during sleep is particularly useful. For example, the respiration signal can be used to infer the person's sleep stages (light, deep or REM sleep) [47,21,39] and diagnose sleep disorders [4,12].…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of RM‐OSM ranges from 76.2% to 80.38%, 227,235–239 with an average accuracy of 79.29%. Moreover, as the specific indicator of RM output, AHI has an accuracy of 93%.…”
Section: Comparison Among Assessment Methodsmentioning
confidence: 99%
“…It was found that the deep learning models performed extremely well in comparison to the probabilistic models. Tataraidze et al (2015), performed a classification task by fetching the data from polysomnography study and classify the sleep, awake, REM, and non-REM. The primary aspect of the work is the addition of some different heuristics, which can increase the performance of the model.…”
Section: Related Workmentioning
confidence: 99%